WCRF-AICR continuous update project: Systematic literature review of prospective studies on circulating 25-hydroxyvitamin D and kidney cancer risk. Issue 164 (November 2016) - Darling, Andrea L.; Abar, Leila; Norat, Teresa
Highlights: A systematic review of studies assessing 25(OH)D status and kidney cancer risk. Four cohort or nested case-control studies and one Pooling Project were included. Subject populations and smoking prevalence may explain between cohort differences. An association between low 25(OH)D and kidney cancer risk could not be ruled out. Abstract: As part of the World Cancer Research Fund/American Institute for Cancer Research (WCRF–AICR) Continuous Update project we performed a systematic review of prospective studies with data for both measured or predicted 25(OH)D concentration and kidney cancer risk. PubMed was searched from inception until 1st December 2014 using WCRF/AICR search criteria. The search identified 4 papers suitable for inclusion, reporting data from three prospective cohort studies, one nested case-control study and the Vitamin D Pooling Project of Rarer Cancers (8 nested case-control studies). Summary effect sizes could not be computed due to incompatibility between studies. All studies except the Pooling Project suggested a reduced risk of kidney cancer by 19–40% with higher or adequate vitamin D status, . However, these estimates only reached statistical significance in one cohort (Copenhagen City Heart Study; CCHS, HR = 0.75 (0.58 to 0.96)). In the European Prospective Investigation into Cancer and Nutrition (EPIC) study, a significant reduction in risk by 18% was seen when using combined matched and non-matched controls OR = 0.82 (0.68, 0.99), but not when using only matched controls (OR = 0.81 (0.65, 1.00). Pooled (but not single cohort) data for predicted 25(OH)D from the Nurses' Health Study (NHS) and Health Professionals Follow-up Study (HPFS) showed a statistically significant reduction in risk by 37% (HR = 0.63 (0.44, 0.91)). There is no clear explanation for the inconsistency of results between studies, but reasons may include prevalence of smoking or other study population characteristics. Methods for assessing circulating 25(OH)D levels and control for confounders including seasonality or hypertension do not seem explanatory.